Finite element method a practical course - Liu, G. R. (Gui-Rong); Quek, S. S. (Oxford : Butterworth-Heinemann, 2003)
The Finite Element Method (FEM) has become an indispensable technology for the modelling and simulation of engineering systems. Written for engineers and students alike, the aim of the book is to provide the necessary theories and techniques of the FEM for readers to be able to use a commercial FEM package to solve primarily linear problems in mechanical and civil engineering with the main focus on structural mechanics and heat transfer. Fundamental theories are introduced in a straightforward way, and state-of-the-art techniques for designing and analyzing engineering systems, including microstructural systems are explained in detail. Case studies are used to demonstrate these theories, methods, techniques and practical applications, and numerous diagrams and tables are used throughout. The case studies and examples use the commercial software package ABAQUS, but the techniques explained are equally applicable for readers using other applications including NASTRAN, ANSYS, MARC, etc. Full sets of PowerPoint slides developed by the authors for their course on FEM are available as a free download from a companion website. * A practical and accessible guide to this complex, yet important subject * Covers modeling techniques that predict how components will operate and tolerate loads, stresses and strains in reality * Full set of PowerPoint presentation slides which illustrate and support the book are available on a companion website.
Computational modelling -- Introduction to mechanics for solids and structures -- Fundamentals for finite element method -- FEM for trusses -- FEM for beams -- FEM for frames -- FEM for two-dimensional solids -- FEM for plates and shells -- FEM for 3D solids -- Special purpose elements -- Modelling techniques -- FEM for heat transfer problems -- Using ABAQUS.
Includes bibliographical references and index.
Keywords: Finite element method; Electronic books